Mysterious Negev Tombs (The Biblical archaeology review, 2025)
In the Northern Negev, at the crossroads of ancient trade routes connecting Egypt and the Levant to the Arabian Peninsula, archaeologists with the Israel Antiquities Authority discovered a mysterious tomb complex dating to sometime between the seventh and fifth centuries BCE. Evidence from the tombs indicates that caravans from as far away as South Arabia […]